Efficacy of Limosilactobacillus fermentum in the management of vulvovaginal candidiasis: comparative analysis with topical miconazole in a single-blind randomized clinical trial - Pane, Marco; Chisari, Emanuele (Frontiers in Microbiology, 2024)
Introduction: Vulvovaginal candidiasis (VVC) significantly impacts women's quality of life and often shows a high recurrence rate despite conventional antifungal therapies. This study evaluates the efficacy of Limosilactobacillus fermentum (LF5), a probiotic, as an alternative treat-ment option to conventional miconazole therapy in managing VVC. The randomized, single-blind clinical trial involved 100 premenopausal women diagnosed with VVC. Participants were assigned to either a vaginal capsule containing LF5 probiotic strain or miconazole. Treatments were administered once daily for three consecutive days. Microbiological eradication of Candida spp. and recurrence rates were assessed at 30 days post-treatment. The trial was registered with the Italian Ministry of Health. Both treatments achieved a high rate of microbiological eradication of Candida spp. within the three-day treatment period (96% for LF5 and 94% for miconazole). Recurrence rates within two weeks posttreatment were low and similar between the groups (10% for LF5 and 17% for miconazole). LF5 was found to have a significantly lower incidence of local adverse reactions compared to miconazole (4% vs. 12%). LF5 presents a viable alternative to miconazole for the treatment of VVC, offering comparable efficacy with fewer side effects. The results suggest that probiotic treatments can potentially enhance patient compliance and quality of life by reducing adverse reactions and recurrence rates. Further research is needed to confirm these findings in larger and more diverse populations.